Mechanisms for improving corporate capital structure management in the Republic of Kazakhstan - Nurgalieva, S.Zh.; Tursynkhanov, D.Zh.; Simonov, S.G. (BUKETOV BUSINESS REVIEW, 2019)
The article is devoted to the issues in the field of the capital structure of the corporation management, maximization of the market value of the enterprise; minimization of the weighted average cost of the enterprise’ capital; minimization of the level of financial risks of the enterprise, activity; maximization of the level of financial profitability. A value management is a process aimed at maximizing the value of the company. It is designed to develop the value thinking of the company’s employees, based on the key value factors. It should improve two-way information exchange, as it allows all the members of the organization «to speak one language that everyone understands». Management of the company’s value consists in the fact that it should be aimed at the ensuring of the company’s market value and its shares growth. The value creation is a universal topic of various methods of improvement, such as total quality management, process-oriented cost management, stocks to be delivered on time, business process re-engineering, time management, etc. The growth of the company’s profits over time creates a value. Companies use a variety of methods to support their growth, from the introduction of new products and services to strategic alliances and the purchase of competitors. Increasing of the return rate is an important way to increase value. Companies must control working capital activities in order to have the necessary funds when they are needed. For a number of organizations, intellectual assets such as patents, trademarks, consumer and supplier relationships, industry knowledge, trained personnel and the knowledge of their company’s peculiarities are in many ways considerably more valuable than their fixed assets, i.e. they increase the market value of the company.